Generalizations of some integral inequalities for fractional integrals - Farid, Ghulam; ur Rehman, Atiq (Annales Mathematicae Silesianae, 2017)
In this paper we give generalizations of the Hadamard-type inequalities for fractional integrals. As special cases we derive several Hadamard type inequalities.